Evaluating the Effect of Monetary Incentives on Web Survey Response Rates in the UK Millennium Cohort Study - Charlotte Booth; Erica Wong; Matt Brown; Emla Fitzsimons (Survey Research Methods)
A major objective for longitudinal studies is retaining participants over time. The Millennium Cohort Study (MCS) is the largest on-going nationally representative study of young people in the UK (N = 18,818). Seven waves of data collection took place face-to-face between 2001 (age 9 months) and 2019 (age 17), with no monetary incentives offered. Throughout 2020 to 2021, participants were invited to take part in three web surveys focused on understanding the impact of the COVID-19 pandemic. In the third web survey, conditional monetary incentives were introduced in the form of a randomised experiment. Three quarters of the issued sample were offered a £10 voucher to complete the survey and the remaining proportion were offered no incentive as usual. Regression analyses were conducted to examine the effect of the incentive on response rates and various aspects of data quality. The incentive boosted the response rate by 7 percentage points, from a baseline of 24%, with a stronger effect observed in those who had taken part in the most recent major wave. Regarding data quality, the incentivised group showed lower break-off rates and spent more time completing the survey. Therefore, the incentive had a significant positive effect on response rates and some aspects of data quality. Future research should evaluate the effect of incentives in relation to other modes of data collection and consider alternative strategies to improve response rates for previous non-respondents, who are considered harder to reach.